PENDAMPINGAN PEMASARAN DIGITAL SEBAGAI UPAYA PENINGKATAN KAPASITAS SUMBER DAYA MANUSIA PADA UMKM KARYA MULIA KOTA PALANGKA RAYA - Mesi Wulandari; Aston Pakpahan (Yayasan Nusa Cendekia Global, 2026)
This community service activity aims to enhance the human resource capacity of Karya Mulia MSMEs in Palangka Raya through digital marketing mentoring. The main challenge faced by these MSMEs is their limited understanding and skills in utilizing digital technology as a marketing tool, resulting in products still being marketed through conventional methods. The activity was implemented through preparation, execution, and evaluation and follow-up phases. The guidance focused on utilizing WhatsApp Business, creating product catalogs, adding business locations to digital platforms, and training on creating simple promotional content. Evaluation was conducted using pre-test and post-test instruments with a Likert scale to measure improvements in the entrepreneurs’ knowledge, skills, and readiness. The results of the activity showed a significant improvement in both respondent groups. Business owners achieved an N-Gain score of 0.82 in the high category, while employees achieved an N-Gain score of 0.76 in the high category. The overall average N-Gain of 0.79 indicates that the mentoring program was effective in enhancing the ability of MSME actors to utilize digital marketing. Thus, the digital marketing mentoring activity was able to improve the knowledge, skills, and confidence of MSME actors in independently marketing their products through digital media.